Digital Culture and Social Media versus the Traditional Education - Poshka, Agim (Journal of Education Culture and Society, 2020)
This article aims to refl ect on the increasing momentum that social media have in the everyday life our students and to investigate the uniqueness that this media offers to the process of education. The study investigates the benefi ts that Facebook and Twitter have as the leading technologically mediated spaces and its application to the learning habitat of the learner in the public pedagogy. The article refl ects on the opportunities that social media offers in order to avoid the self-created intellectual chamber by allowing educators to share and challenge ideas and concepts through the so called non-traditional “great spare time revolution”.